Subspecies distribution and drug-resistance characteristics of Mycobacterium abscessus complex clinical isolates in South China - Xinyu Wang; Biyi Su; Pinru Chen; Haobin Kuang; Ping Guan; Chao Zhang; Liping Pan; Jialou Zhu; Yaoju Tan (Microbiology Spectrum)
ABSTRACT Mycobacterium abscessus complex (MABC) is the most common rapidly growing non-tuberculous mycobacterium (NTM) and a significant pathogen responsible for various infections. Subspecies of MABC exhibit differing levels of antibiotic resistance, potentially influencing patient prognosis. In this study, 196 MABC clinical isolates were collected from Guangzhou Chest Hospital and subjected to a drug sensitivity test (DST) followed by whole-genome sequencing. In our study, the most common subspecies was Mycobacterium abscessus subsp. abscessus, followed by M. abscessus subsp. massiliense, with M. abscessus subsp. bolletii being the least frequent. The isolates were most susceptible to tigecycline and amikacin, followed by clarithromycin and linezolid. Bedaquiline and clofazimine showed promising anti-bacterial activity, whereas doramapimod and capreomycin demonstrated limited efficacy. The erm(41) gene mutation at position 28 and the rrl gene at position 2270 were identified in clarithromycin-resistant isolates. Additionally, the rrs gene mutation at position 1375 may serve as an indicator of amikacin resistance. Regular molecular surveillance investigation of NTM and DST is recommended for improved management.IMPORTANCEAs Guangdong is a region with a high prevalence of NTM, this study investigates the epidemiological trends of MABC subspecies and their associated drug-resistance profiles, addressing a critical research gap. The findings are crucial for guiding hospital drug management and clinical decision making, enabling more accurate diagnoses and the formulation of personalized, effective treatment plans. Additionally, this study provides a valuable reference for the development of drug-resistance detection reagents and new anti-bacterial agents.